Karst hazard assessment in the design of the main gas pipeline (South Yakutia) - Strokova, Ludmila Aleksandrovna; Dutova, Ekaterina Matveevna; Ermolaeva, A.V.; Alimova, I.N.; Strelnikova, Anna Borisovna (IOP Publishing, 2015)
The paper represents the description of the zonal and regional geological factors of geoengineering conditions which characterize the territory in South Yakutia crossed by the designed main gas pipeline. Cryogenic processes and karst are considered to be the most dangerous hazards for gas pipeline maintenance. Karst hazard assessment of the gas pipeline section made in the course of the research has involved a complex of geological methods: geoengineering, geophysical, hydrogeological, and mapping. Sections prone to karst development have been identified. The authors have suggested the measures to protect potentially hazardous sections and to ensure timely informing on sinkhole collapses.
Keywords: карст; магистральные газопроводы; Южная Якутия; карстовые процессы; газопроводы